Microstructural Study Of Fakfak Local Aggregates Using Sem-EDS: Implications For The Durability Of Modern Concrete - Attamimi, Aqilah; Imran, Imran (Community Engagement and Emergence Journal (CEEJ), 2025)
This study investigates the properties of Fakfak local aggregates and explores their potential use in concrete applications. The aggregates were characterized using Scanning Electon Microscopy (SEM) to asses they chemical composition and microstructural features. The SEM analysis showed notable porosity and microcracks, indicating potential weaknesses. The results revealed that Fakfak local Aggregates exhibit porous morphologies with a considerable calcium (CaO) content. Such differences in elemental composition and morphology have significant implications for concrete durability. The findings highlight that aggregates containing CaO and adequate surface porosity promote calcite precipitation and provide pore spaces that facilitate crack healing. Accordingly, this kind of Aggregates demonstrate greater potential as concrete admixtures, and also offering promising prospects for enhancing the durability and self-healing capacity of modern concrete. Despite these challenges, the study suggests that with appropriate treatments, such as the use of supplementary cementious materials these aggregates could be effectively utilized in concrete, contributing to sustainable construction pratices. The findings underscore the importance of targeted reinforcement strategies to enhance aggregate performance and recommend further research on long-term durability and environmental impacts.